Muslims and Ecology: Residential Area Development in Semarang Perspective of Islamic and Social Environmental Ethics - Laeli Muftichana (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2022)
This study aims to describe the development and regional environmental management in the Bukit Semarang Baru Satellite City (BSB) from an Islamic perspective and environmental sociology. This type of research is qualitative with a case study approach. The research data is on the construction of a new Semarang hill. Data collection techniques were carried out through observation and interviews. At the same time, data analysis is done by data reduction, data presentation, and concluding. The study results show that the management of BSB City has provided several facilities to the people who occupy the housing. However, the development of this area also brought postive and negative impacts on the community around the area.